ASSOCIAÇÃO ENTRE A METILAÇÃO DO GENE NR3C1 E A SÍNDROME METABÓLICA EM ADULTOS ATENDIDOS PELO SUS - Olinda, Amanda Sgrancio (2022)
Metabolic syndrome (MS) is characterized by a set of risk factors, such as excess abdominal fat, low HDL cholesterol levels, high triglycerides, high blood pressure and high glucose. Due to its complexity and multifactorial characteristics, in addition to environmental factors and genetics, epigenetics may also be involved in the development of metabolic syndrome. Therefore, the objective of this study was to evaluate the determining factors of MS and NR3C1 gene methylation in the promoter region (1F) and to investigate its relationship with SM. Thus, a cross-sectional study was carried out with 353 adult volunteers assisted by SUS. Data collection was carried out using a socioeconomic, lifestyle and, health status questionnaire. Anthropometric data, blood pressure measurements and blood samples were also collected for biochemical and molecular analyses. The extracted DNA was amplified by polymerase chain reaction (PCR) and then subjected to pyrosequencing to determine the methylation profile of the NR3C1 gene. According to Poisson's multivariate analysis with robust variance, the determining factors for metabolic syndrome (p<0.05) were body fat, VLDL cholesterol, and methylation in CpGs 6, 8, 10, and 12 of the NR3C1 gene. In addition, the prevalence of metabolic syndrome in the sample was 23.22%. The data found in this research reinforce the possible epigenetic involvement of the NR3C1 gene with metabolic syndrome.